7+3(4x-4)=6-5(2x+1)

Simple and best practice solution for 7+3(4x-4)=6-5(2x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7+3(4x-4)=6-5(2x+1) equation:


Simplifying
7 + 3(4x + -4) = 6 + -5(2x + 1)

Reorder the terms:
7 + 3(-4 + 4x) = 6 + -5(2x + 1)
7 + (-4 * 3 + 4x * 3) = 6 + -5(2x + 1)
7 + (-12 + 12x) = 6 + -5(2x + 1)

Combine like terms: 7 + -12 = -5
-5 + 12x = 6 + -5(2x + 1)

Reorder the terms:
-5 + 12x = 6 + -5(1 + 2x)
-5 + 12x = 6 + (1 * -5 + 2x * -5)
-5 + 12x = 6 + (-5 + -10x)

Combine like terms: 6 + -5 = 1
-5 + 12x = 1 + -10x

Solving
-5 + 12x = 1 + -10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '10x' to each side of the equation.
-5 + 12x + 10x = 1 + -10x + 10x

Combine like terms: 12x + 10x = 22x
-5 + 22x = 1 + -10x + 10x

Combine like terms: -10x + 10x = 0
-5 + 22x = 1 + 0
-5 + 22x = 1

Add '5' to each side of the equation.
-5 + 5 + 22x = 1 + 5

Combine like terms: -5 + 5 = 0
0 + 22x = 1 + 5
22x = 1 + 5

Combine like terms: 1 + 5 = 6
22x = 6

Divide each side by '22'.
x = 0.2727272727

Simplifying
x = 0.2727272727

See similar equations:

| x*sqrt(x-3)=4 | | x^2+0.5x-0.01=0 | | 8=8x+8 | | 3+4(5x-6)=6-4(2x+1) | | h(x)=2x^2+x-10 | | x^2-7xy+6y^2= | | y-8=-5(x+1) | | 6=k(12) | | 2.96x-2.6=-3.47x+7.47 | | 10p-3(3p-6)=4(3p-6)-8p | | y=10-2(y-4) | | -18x^2+61xy+7y^2=0 | | 2x^2=6p-20 | | 2z=4z-8 | | 2x^2-6p=-20 | | V-7+1=14+5v | | log5(x^4y^9/6) | | 4x-101=12x-53 | | 7y=4y+9 | | 8-4x=-10+x | | f(x)=senx | | 0.25m+0.75m=2 | | 6x^2-13x+0=0 | | 4x-201=12x-53 | | 5-(-3y)=-9y+3y | | -7/9x=28 | | -4s=-12 | | X^2y-3x^2= | | -18x^2-65xa-7a^2=0 | | 43=15+0.5x | | 2cosx-sin^2x+2=0 | | 4z-7/3z-3z-5/4z |

Equations solver categories